Constructing a Scale of Attitudes toward School Science Using the General Graded Unfolding Model - Taghreed Hijazi; Zaid Bani Ata (Sultan Qaboos University, 2013)
The present study aimed at constructing an attitude scale toward school science using the generalized graded unfolding model (GGUM). A 47-item scale (24 positive, 23 negative) with 4-point response format was used to measure attitudes toward science among 9th  (n=424) and 10th (n=420) grade students in 38 sections distributed randomly over 22 schools in Irbid district. Respondents selected one of four options to represent their level of agreement with each item. The findings support the hypothesis that the data form a single unidimensional unfolding model. Furthermore, the findings showed that the GGUM didn't fit the data of 7 items, leaving the final scale with 40 items, where accurate estimates of these item parameters were derived and the GGUM was appropriate. Cronbach's alpha for the internal consistency, and the test retest reliability coefficients of the final scale were 0.932 and 0.875, respectively.